Improving Indonesian Language Learning Results About Characters and Assignments Through Problem Based Learning Learning Models In SDN 01 Banjaranyar - Agus Syukron (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve the learning outcomes of students in the Indonesian language muple in grade IV elementary schools with the Problem Based Learning (PBL) learning model. The research conducted was a Classroom Action Research (CAR) in two cycles, with each cycle consisting of two meetings. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle the students who completed after carrying out the post test were 53%. In cycle II students who completed after carrying out the post test were 90%. These results indicate that the Problem Based Learning (PBL) learning model can improve the learning outcomes of students, especially Class IV Indonesian language muple at SDN 01 Banjaranyar.